2021
DOI: 10.3390/pharmaceutics14010012
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Pullulan–Dexamethasone Conjugates in Retinal Drug Delivery

Abstract: The treatment of retinal diseases by intravitreal injections requires frequent administration unless drug delivery systems with long retention and controlled release are used. In this work, we focused on pullulan (≈67 kDa) conjugates of dexamethasone as therapeutic systems for intravitreal administration. The pullulan–dexamethasone conjugates self-assemble into negatively charged nanoparticles (average size 326 ± 29 nm). Intravitreal injections of pullulan and pullulan–dexamethasone were safe in mouse, rat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…Reservoirs were designed to maintain large, fluidic volumes for multi-day testing, and the electrode assembly can apply a range of electrical fields to stimulate SC motility ( Figure 5 ). This design facilitates the application of electric fields currently used in animal studies and in the clinic, such as treatments with biochemical agents [ 76 , 77 ] and low level electric fields [ 78 , 79 ]. Electrical activity is known to play an important role in the formation and connectivity of neural circuits, where EF can modify synaptic connectivity, the structure of neuronal projections, and induce changes in gene expression, protein synthesis, and intrinsic excitability (reviewed in [ 80 , 81 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reservoirs were designed to maintain large, fluidic volumes for multi-day testing, and the electrode assembly can apply a range of electrical fields to stimulate SC motility ( Figure 5 ). This design facilitates the application of electric fields currently used in animal studies and in the clinic, such as treatments with biochemical agents [ 76 , 77 ] and low level electric fields [ 78 , 79 ]. Electrical activity is known to play an important role in the formation and connectivity of neural circuits, where EF can modify synaptic connectivity, the structure of neuronal projections, and induce changes in gene expression, protein synthesis, and intrinsic excitability (reviewed in [ 80 , 81 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The μ-Eye represents the first bioengineering system to integrate microfluidic environments with models of whole, enucleated eyes [ 72 ]. This is a significant step towards using in vitro and ex vivo technologies to aid development of in vivo strategies for transplantation, such as the use of EF and/electrodes [ 84 ], biomaterials [ 85 ], or pharmacological injection [ 77 ]. While a variety of in vitro and ex vivo platforms have been developed to examine SC behaviors (reviewed in [ 82 , 86 ]), the μ-Eye can bridge microfluidics with ocular explants to build hybrid, quantitative platforms for transplantation study in adult tissue environments.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that these pullulan-based drug conjugates are safe in rabbit, mouse, and rat eyes, have a long residence time in the vitreous, and are approximately wholly eliminated through the aqueous humor outflow. The findings of this study revealed that pullulan–dexamethasone conjugates might release active and free dexamethasone in the vitreous humor for higher than 16 days, although a big dexamethasone fraction might be deleted from the eye as bound pullulan–dexamethasone [ 162 ].…”
Section: Applications Of Nano-based Materials For Ocular Drug Deliverymentioning
confidence: 99%
“…Regarding all reported polysaccharide-based materials for treating eye disorders, it seems that the therapeutic system reported by Eva Kicková and coworkers provides great intravitreal drug delivery systems because they could diminish the frequency of injection and transfer of drugs into retinal tissues. Besides, this nanoplatform showed good biosafety and long residence time in the vitreous [ 162 ]. Also, the nanogels-based on chitosan reported by Buosi et al offered successful nanocarriers delivery systems with respect to non-cytotoxic and non-inflammatory effects in human ARPE-19 cells, opening the good opportunity for its use in ocular disease [ 157 ].…”
Section: Applications Of Nano-based Materials For Ocular Drug Deliverymentioning
confidence: 99%
“…24 The obtained in vitro release rate constant (k) of dexamethasone from the PNADEX-CA hydrogel was used for simulation of intravitreal pharmacokinetics of dexamethasone in humans. Pharmacokinetics were simulated using a compartmental model reported and validated in the literature for vitreal kinetics of sustained release of dexamethasone from nanomaterials (Supporting Information, Figure S1) 25,26 using the parameters shown in Table S1. When applicable, parameters for dexamethasone phosphate were used in the model, due to the lack of available reported kinetic parameters for dexamethasone in the literature.…”
Section: Release Of Dexamethasone From the Hydrogel And Intravitreal ...mentioning
confidence: 99%